Identification of Aeromonas hydrophila Genes Preferentially Expressed after Phagocytosis by Tetrahymena and Involvement of Methionine Sulfoxide Reductases - Pang, Maoda; Lin, Xiaoqin; Liu, Jin; Guo, Changming; Gao, Shanshan; Du, Hechao; Lu, Chengping; Liu, Yongjie (Frontiers in Cellular and Infection Microbiology, 2016)
Free-living protozoa affect the survival and virulence evolution of pathogens in the environment. In this study, we explored the fate of Aeromonas hydrophila when co-cultured with the bacteriovorous ciliate Tetrahymena thermophila and investigated bacterial gene expression associated with the co-culture. Virulent A. hydrophila strains were found to have ability to evade digestion in the vacuoles of this protozoan. In A. hydrophila, a total of 116 genes were identified as up-regulated following co-culture with T. thermophila by selective capture of transcribed sequences (SCOTS) and comparative dot-blot analysis. A large proportion of these genes (42/116) play a role in metabolism, and some of the genes have previously been characterized as required for bacterial survival and replication within macrophages. Then, we inactivated the genes encoding methionine sulfoxide reductases, msrA, and msrB, in A. hydrophila. Compared to the wild-type, the mutants ΔmsrA and ΔmsrAB displayed significantly reduced resistance to predation by T. thermophila, and 50% lethal dose (LD50) determinations in zebrafish demonstrated that both mutants were highly attenuated. This study forms a solid foundation for the study of mechanisms and implications of bacterial defenses.